Lipolysis and fat oxidation are not altered with presleep compared with daytime casein protein intake in resistance-trained women - Allman, B. R.; Morrissey, M. C.; Kim, J.-S.; Panton, L. B.; Contreras, R. J.; Hickner, R. C.; Ormsbee, M. J. (The Journal of Nutrition, 2019)
Background: To date, no studies have directly compared the differences between presleep and daytime protein (PRO) consumption on localized and systemic fat metabolism in active women. Objective: The purpose of this study was to assess the effects of presleep compared with daytime PRO supplementation on subcutaneous abdominal adipose tissue (SCAAT) lipolysis and whole-body substrate utilization in women. Methods: Thirteen young (mean ± SE age: 22 ± 1 y; BMI: 24.3 ± 0.8 kg/m2), resistance-trained [1 repetition maximum (1RM) squat percentage of body weight: 135% ± 6%; 1RM bench press percentage of body weight: 82% ± 4%] women volunteered. On overnight experimental visits, participants performed full-body resistance exercise (RE; 65% 1RM) and were randomly assigned to consume either daytime PRO (PRO, 30 g casein) 30 min post-RE and presleep (30 min before bed) noncaloric, sensory-matched placebo (PLA, 0 g casein) (PRO-PLA), or the opposite (PLA-PRO), switching the order of the supplements on the following visit. SCAAT lipolysis, resting metabolism (indirect calorimetry), and plasma biomarkers (glucose, insulin, nonesterified fatty acids, glycerol) were measured at baseline, overnight, and the next morning. Results: There were no differences in overnight SCAAT lipolysis between conditions indicated by interstitial glycerol concentrations (PRO-PLA: baseline, 669 ± 137; next morning, 321 ± 77.1; PLA-PRO: baseline, 524 ± 109; next morning, 333 ± 68.0 µM), fat oxidation (PRO-PLA: baseline, 5.70 ± 0.35; next morning, 5.00 ± 0.28; PLA-PRO: baseline, 6.59 ± 0.32; next morning, 5.44 ± 0.27 g/min), or any other measure. Conclusions: There was no difference between the effects of daytime and presleep PRO supplementation on SCAAT lipolysis or whole-body substrate utilization in resistance-trained women. Presleep PRO is a viable option for increasing PRO consumption in resistance-trained women because it does not blunt overnight lipolysis, and will therefore likely not lead to increases in subcutaneous abdominal fat